Size-selected Fe3O4–Au hybrid nanoparticles for improved magnetism-based theranostics - Efremova, Maria V.; Nalench, Yulia A.; Myrovali, Eirini; Garanina, Anastasiia S.; Grebennikov, Ivan S.; Gifer, Polina K.; Abakumov, Maxim A.; Spasova, Marina; Angelakeris, Makis; Savchenko, Alexander G.; Farle, Michael; Klyachko, Natalia L.; et al. (Beilstein Journal of Nanotechnology, 2018)
Size-selected Fe3O4–Au hybrid nanoparticles with diameters of 6–44 nm (Fe3O4) and 3–11 nm (Au) were prepared by high temperature, wet chemical synthesis. High-quality Fe3O4 nanocrystals with bulk-like magnetic behavior were obtained as confirmed by the presence of the Verwey transition. The 25 nm diameter Fe3O4–Au hybrid nanomaterial sample (in aqueous and agarose phantom systems) showed the best characteristics for application as contrast agents in magnetic resonance imaging and for local heating using magnetic particle hyperthermia. Due to the octahedral shape and the large saturation magnetization of the magnetite particles, we obtained an extraordinarily high r2-relaxivity of 495 mM−1·s−1 along with a specific loss power of 617 W·gFe−1 and 327 W·gFe−1 for hyperthermia in aqueous and agarose systems, respectively. The functional in vitro hyperthermia test for the 4T1 mouse breast cancer cell line demonstrated 80% and 100% cell death for immediate exposure and after precultivation of the cells for 6 h with 25 nm Fe3O4–Au hybrid nanomaterials, respectively. This confirms that the improved magnetic properties of the bifunctional particles present a next step in magnetic-particle-based theranostics.
Keywords: hybrid nanoparticles; magnetic hyperthermia; magnetic resonance imaging; nanomagnetism; theranostics

(untitled) - Ferrari, M. (Nat. Rev. Cancer, 2005)

(untitled) - Cho, K.; Wang, X.; Nie, S.; Chen, Z.; Shin, D. M. (Clin. Cancer Res., 2008)

(untitled) - Ma, Y.; Huang, J.; Song, S.; Chen, H.; Zhang, Z. (Small, 2016)

(untitled) - Master, A. M.; Williams, P. N.; Pothayee, N.; Zhang, R.; Vishwasrao, H. M.; Golovin, Y. I.; Riffle, J. S.; Sokolsky, M.; Kabanov, A. V. (Sci. Rep., 2016)

Nanoscience: Nanostructures through Chemistry - Ortega, D.; Pankhurst, Q. A. (Magnetic hyperthermia., 2013)

(untitled) - Myrovali, E.; Maniotis, N.; Makridis, A.; Terzopoulou, A.; Ntomprougkidis, V.; Simeonidis, K.; Sakellari, D.; Kalogirou, O.; Samaras, T.; Salikhov, R.; Spasova, M.; Farle, M.; et al. (Sci. Rep., 2016)

(untitled) - Périgo, E. A.; Hemery, G.; Sandre, O.; Ortega, D.; Garaio, E.; Plazaola, F.; Teran, F. J. (Appl. Phys. Rev., 2015)

(untitled) - Leung, K. C.-F.; Xuan, S.; Zhu, X.; Wang, D.; Chak, C.-P.; Lee, S.-F.; Ho, W. K.-W.; Chung, B. C.-T. (Chem. Soc. Rev., 2012)

(untitled) - Pu, F.; Salarian, M.; Xue, S.; Qiao, J.; Feng, J.; Tan, S.; Patel, A.; Li, X.; Mamouni, K.; Hekmatyar, K.; Zou, J.; Wu, D.; et al. (Nanoscale, 2016)

(untitled) - Tomitaka, A.; Arami, H.; Raymond, A.; Yndart, A.; Kaushik, A.; Jayant, R. D.; Takemura, Y.; Cai, Y.; Toborek, M.; Nair, M. (Nanoscale, 2017)

(untitled) - Khandhar, A. P.; Ferguson, R. M.; Arami, H.; Krishnan, K. M. (Biomaterials, 2013)

(untitled) - Yu, E. Y.; Bishop, M.; Zheng, B.; Ferguson, R. M.; Khandhar, A. P.; Kemp, S. J.; Krishnan, K. M.; Goodwill, P. W.; Conolly, S. M. (Nano Lett., 2017)

(untitled) - Lee, J.-H.; Lee, K.; Moon, S. H.; Lee, Y.; Park, T. G.; Cheon, J. (Angew. Chem., Int. Ed., 2009)

(untitled) - Ulbrich, K.; Holá, K.; Šubr, V.; Bakandritsos, A.; Tuček, J.; Zbořil, R. (Chem. Rev., 2016)

(untitled) - Fernandes Cardoso, V.; Francesko, A.; Ribeiro, C.; Bañobre-López, M.; Martins, P.; Lanceros-Mendez, S. (Adv. Healthcare Mater., 2018)

(untitled) - De Crozals, G.; Bonnet, R.; Farre, C.; Chaix, C. (Nano Today, 2016)

(untitled) - Mosayebi, J.; Kiyasatfar, M.; Laurent, S. (Adv. Healthcare Mater., 2017)

(untitled) - Wiedwald, U.; Ziemann, P. (Beilstein J. Nanotechnol., 2010)

(untitled) - Guardia, P.; Labarta, A.; Batlle, X. (J. Phys. Chem. C, 2011)

(untitled) - Baaziz, W.; Pichon, B. P.; Fleutot, S.; Liu, Y.; Lefevre, C.; Greneche, J.-M.; Toumi, M.; Mhiri, T.; Begin-Colin, S. (J. Phys. Chem. C, 2014)

(untitled) - Brollo, M. E. F.; López-Ruiz, R.; Muraca, D.; Figueroa, S. J. A.; Pirota, K. R.; Knobel, M. (Sci. Rep., 2014)

(untitled) - Pineider, F.; de Julián Fernández, C.; Videtta, V.; Carlino, E.; al Hourani, A.; Wilhelm, F.; Rogalev, A.; Cozzoli, P. D.; Ghigna, P.; Sangregorio, C. (ACS Nano, 2013)

(untitled) - Thi Thuy, N.; Mammeri, F.; Ammar, S. (Nanomaterials, 2018)

(untitled) - Fazal, S.; Paul-Prasanth, B.; Nair, S. V.; Menon, D. (ACS Appl. Mater. Interfaces, 2017)

(untitled) - Schick, I.; Lorenz, S.; Gehrig, D.; Tenzer, S.; Storck, W.; Fischer, K.; Strand, D.; Laquai, F.; Tremel, W. (Beilstein J. Nanotechnol., 2014)

(untitled) - Efremova, M. V.; Veselov, M. M.; Barulin, A. V.; Gribanovsky, S. L.; Le-Deygen, I. M.; Uporov, I. V.; Kudryashova, E. V.; Sokolsky-Papkov, M.; Majouga, A. G.; Golovin, Y. I.; Kabanov, A. V.; Klyachko, N. L. (ACS Nano, 2018)

(untitled) - Rudakovskaya, P. G.; Lebedev, D. N.; Efremova, M. V.; Beloglazkina, E. K.; Zyk, N. V.; Klyachko, N. L.; Golovin, Y. I.; Savchenko, A. G.; Mazhuga, A. G. (Nanotechnol. Russ., 2016)

(untitled) - Angelakeris, M. (Biochim. Biophys. Acta, Gen. Subj., 2017)

(untitled) - Liu, S.; Guo, S. J.; Sun, S.; You, X.-Z. (Nanoscale, 2015)

(untitled) - Zhai, Y.; Jin, L.; Wang, P.; Dong, S. (Chem. Commun., 2011)

(untitled) - Salikhov, S. V.; Savchenko, A. G.; Grebennikov, I. S.; Yurtov, E. V. (Bull. Russ. Acad. Sci.: Phys., 2015)

(untitled) - Wang, C.; Yin, H.; Dai, S.; Sun, S. (Chem. Mater., 2010)

(untitled) - Sorenson, T. A.; Morton, S. A.; Waddill, G. D.; Switzer, J. A. (J. Am. Chem. Soc., 2002)

(untitled) - Verwey, E. J. W. (Nature, 1939)

(untitled) - Aragón, R. (Phys. Rev. B, 1992)

(untitled) - Salazar, J. S.; Perez, L.; de Abril, O.; Lai Truong, P.; Ihiawakrim, D.; Vazquez, M.; Greneche, J.-M.; Begin-Colin, S.; Pourroy, G. (Chem. Mater., 2011)

(untitled) - Andrés Vergés, M.; Costo, R.; Roca, A. G.; Marco, J. F.; Goya, G. F.; Serna, C. J.; Morales, M. P. (J. Phys. D: Appl. Phys., 2008)

(untitled) - Witt, A.; Fabian, K.; Bleil, U. (Earth Planet. Sci. Lett., 2005)

(untitled) - Fabian, K.; Kirchner, A.; Williams, W.; Heider, F.; Leibl, T.; Hubert, A. (Geophys. J. Int., 1996)

(untitled) - Goya, G. F.; Berquó, T. S.; Fonseca, F. C.; Morales, M. P. (J. Appl. Phys., 2003)

(untitled) - Park, J.; Lee, E.; Hwang, N.-M.; Kang, M.; Kim, S. C.; Hwang, Y.; Park, J.-G.; Noh, H. J.; Kini, J. Y.; Park, J. H.; Hyeon, T. (Angew. Chem., Int. Ed., 2005)

(untitled) - Omelyanchik, A.; Levada, E.; Ding, J.; Lendinez, S.; Pearson, J.; Efremova, M.; Bessalova, V.; Karpenkov, D.; Semenova, E.; Khlusov, I.; Litvinova, L.; Abakumov, M.; et al. (IEEE Trans. Magn., 2018)

(untitled) - Demortiére, A.; Panissod, P.; Pichon, B. P.; Pourroy, G.; Guillon, D.; Donnio, B.; Bégin-Colin, S. (Nanoscale, 2011)

(untitled) - Töpfer, J.; Angermann, A. (Mater. Chem. Phys., 2011)

(untitled) - Wang, J.; Peng, Z.; Huang, Y.; Chen, Q. (J. Cryst. Growth, 2004)

(untitled) - Berkowitz, A. E.; Schuele, W. J.; Flanders, P. J. (J. Appl. Phys., 1968)

(untitled) - Sharrock, M. P. (J. Appl. Phys., 1994)

(untitled) - Kuerbanjiang, B.; Wiedwald, U.; Haering, F.; Biskupek, J.; Kaiser, U.; Ziemann, P.; Herr, U. (Nanotechnology, 2013)

(untitled) - Liébana-Viñas, S.; Wiedwald, U.; Elsukova, A.; Perl, J.; Zingsem, B.; Semisalova, A. S.; Salgueiriño, V.; Spasova, M.; Farle, M. (Chem. Mater., 2015)

(untitled) - Wiedwald, U.; Han, L.; Biskupek, J.; Kaiser, U.; Ziemann, P. (Beilstein J. Nanotechnol., 2010)

(untitled) - Massner, C.; Sigmund, F.; Pettinger, S.; Seeger, M.; Hartmann, C.; Ivleva, N. P.; Niessner, R.; Fuchs, H.; Hrabě de Angelis, M.; Stelzl, A.; Koonakampully, N. L.; Rolbieski, H.; et al. (Adv. Funct. Mater., 2018)

(untitled) - Martínez, B.; Roig, A.; Obradors, X.; Molins, E.; Rouanet, A.; Monty, C. (J. Appl. Phys., 1996)

Magnetic Oxides - Craik, D. J. (Wiley & Sons, 1975)

(untitled) - Winklhofer, M.; Fabian, K.; Heider, F. (J. Geophys. Res.: Solid Earth, 1997)

(untitled) - Liébana-Viñas, S.; Simeonidis, K.; Wiedwald, U.; Li, Z.-A.; Ma, Z.; Myrovali, E.; Makridis, A.; Sakellari, D.; Vourlias, G.; Spasova, M.; Farle, M.; Angelakeris, M. (RSC Adv., 2016)

(untitled) - Shao, H.; Yoon, T.-J.; Liong, M.; Weissleder, R.; Lee, H. (Beilstein J. Nanotechnol., 2010)

(untitled) - Ni, D. L.; Bu, W. B.; Ehlerding, E. B.; Cai, W. B.; Shi, J. L. (Chem. Soc. Rev., 2017)

(untitled) - Lee, N.; Hyeon, T. (Chem. Soc. Rev., 2012)

(untitled) - Blanco-Andujar, C.; Walter, A.; Cotin, G.; Bordeianu, C.; Mertz, D.; Felder-Flesch, D.; Begin-Colin, S. (Nanomedicine (London, U. K.), 2016)

(untitled) - Laurent, S.; Forge, D.; Port, M.; Roch, A.; Robic, C.; Elst, L. V.; Muller, R. N. (Chem. Rev., 2008)

(untitled) - Poeselt, E.; Kloust, H.; Tromsdorf, U.; Janschel, M.; Hahn, C.; Masslo, C.; Weller, H. (ACS Nano, 2012)

(untitled) - Jun, Y. W.; Huh, Y. M.; Choi, J. S.; Lee, J. H.; Song, H. T.; Kim, S.; Yoon, S.; Kim, K. S.; Shin, J. S.; Suh, J. S.; Cheon, J. (J. Am. Chem. Soc., 2005)

(untitled) - Paquet, C.; de Haan, H. W.; Leek, D. M.; Lin, H.-Y.; Xiang, B.; Tian, G.; Kell, A.; Simard, B. (ACS Nano, 2011)

(untitled) - Huang, J.; Bu, L.; Xie, J.; Chen, K.; Cheng, Z.; Li, X.; Chen, X. (ACS Nano, 2010)

(untitled) - Reguera, J.; Jiménez de Aberasturi, D.; Henriksen-Lacey, M.; Langer, J.; Espinosa, A.; Szczupak, B.; Wilhelm, C.; Liz-Marzán, L. M. (Nanoscale, 2017)

(untitled) - Vuong, Q. L.; Berret, J.-F.; Fresnais, J.; Gossuin, Y.; Sandre, O. (Adv. Healthcare Mater., 2012)

(untitled) - de la Presa, P.; Luengo, Y.; Multigner, M.; Costo, R.; Morales, M. P.; Rivero, G.; Hernando, A. (J. Phys. Chem. C, 2012)

(untitled) - Chen, Z.-J.; Broaddus, W. C.; Viswanathan, R. R.; Raghavan, R.; Gillies, G. T. (IEEE Trans. Biomed. Eng., 2002)

(untitled) - Salloum, M.; Ma, R. H.; Weeks, D.; Zhu, L. (Int. J. Hyperthermia, 2008)

(untitled) - Kim, D.; Yu, M. K.; Lee, T. S.; Park, J. J.; Jeong, Y. Y.; Jon, S. (Nanotechnology, 2011)

(untitled) - Li, W.; Tutton, S.; Vu, A. T.; Pierchala, L.; Li, B. S. Y.; Lewis, J. M.; Prasad, P. V.; Edelman, R. R. (J. Magn. Reson. Imaging, 2005)

(untitled) - Choi, D.; Han, A.; Park, J. P.; Kim, J. K.; Lee, J. H.; Kim, T. H.; Kim, S.-W. (Small, 2009)

(untitled) - Hwang, L. P.; Freed, J. H. (J. Chem. Phys., 1975)

(untitled) - Joshi, H. M.; Lin, Y. P.; Aslam, M.; Prasad, P. V.; Schultz-Sikma, E. A.; Edelman, R.; Meade, T.; Dravid, V. P. (J. Phys. Chem. C, 2009)

(untitled) - Smolensky, E. D.; Park, H.-Y. E.; Zhou, Y.; Rolla, G. A.; Marjańska, M.; Botta, M.; Pierre, V. C. (J. Mater. Chem. B, 2013)

(untitled) - Lee, N.; Choi, Y.; Lee, Y.; Park, M.; Moon, W. K.; Choi, S. H.; Hyeon, T. (Nano Lett., 2012)

(untitled) - Zhao, Z.; Zhou, Z.; Bao, J.; Wang, Z.; Hu, J.; Chi, X.; Ni, K.; Wang, R.; Chen, X.; Chen, Z.; Gao, J. (Nat. Commun., 2013)

(untitled) - Zhou, Z.; Zhao, Z.; Zhang, H.; Wang, Z.; Chen, X.; Wang, R.; Chen, Z.; Gao, J. (ACS Nano, 2014)

(untitled) - Bakoglidis, K. D.; Simeonidis, K.; Sakellari, D.; Stefanou, G.; Angelakeris, M. (IEEE Trans. Magn., 2012)

(untitled) - Hergt, R.; Hiergeist, R.; Zeisberger, M.; Schüler, D.; Heyen, U.; Hilger, I.; Kaiser, W. A. (J. Magn. Magn. Mater., 2005)

(untitled) - Di Corato, R.; Espinosa, A.; Lartigue, L.; Tharaud, M.; Chat, S.; Pellegrino, T.; Ménager, C.; Gazeau, F.; Wilhelm, C. (Biomaterials, 2014)

(untitled) - Guardia, P.; Nitti, S.; Materia, M. E.; Pugliese, G.; Yaacoub, N.; Greneche, J.-M.; Lefevre, C.; Manna, L.; Pellegrino, T. (J. Mater. Chem. B, 2017)

(untitled) - Simeonidis, K.; Martinez-Boubeta, C.; Balcells, L.; Monty, C.; Stavropoulos, G.; Mitrakas, M.; Matsakidou, A.; Vourlias, G.; Angelakeris, M. (J. Appl. Phys., 2013)

(untitled) - Efremova, M. V.; Naumenko, V. A.; Spasova, M.; Garanina, A. S.; Abakumov, M. A.; Blokhina, A. D.; Melnikov, P. A.; Prelovskaya, A. O.; Heidelmann, M.; Li, Z.-A.; Ma, Z.; Shchetinin, I. V.; et al. (Sci. Rep., 2018)

(untitled) - Xu, C.; Xie, J.; Ho, D.; Wang, C.; Kohler, N.; Walsh, E. G.; Morgan, J. R.; Chin, Y. E.; Sun, S. (Angew. Chem., Int. Ed., 2008)

(untitled) - Simon, H. U.; Haj-Yehia, A.; Levi-Schaffer, F. (Apoptosis, 2000)

(untitled) - Circu, M. L.; Aw, T. Y. (Free Radical Biol. Med., 2010)

(untitled) - Erofeev, A.; Gorelkin, P.; Garanina, A.; Alova, A.; Efremova, M.; Vorobyeva, N.; Edwards, C.; Korchev, Y.; Majouga, A. (Sci. Rep., 2018)

(untitled) - Soenen, S. J.; Rivera-Gil, P.; Montenegro, J.-M.; Parak, W. J.; De Smedt, S. C.; Braeckmans, K. (Nano Today, 2011)

(untitled) - Sadhukha, T.; Wiedmann, T. S.; Panyam, J. (Biomaterials, 2014)

(untitled) - Guardia, P.; Di Corato, R.; Lartigue, L.; Wilhelm, C.; Espinosa, A.; Garcia-Hernandez, M.; Gazeau, F.; Manna, L.; Pellegrino, T. (ACS Nano, 2012)

(untitled) - Asín, L.; Ibarra, M. R.; Tres, A.; Goya, G. F. (Pharm. Res., 2012)

(untitled) - Sanchez, C.; El Hajj Diab, D.; Connord, V.; Clerc, P.; Meunier, E.; Pipy, B.; Payré, B.; Tan, R. P.; Gougeon, M.; Carrey, J.; Gigoux, V.; Fourmy, D. (ACS Nano, 2014)

(untitled) - Oh, Y.; Lee, N.; Kang, H. W.; Oh, J. (Nanotechnology, 2016)

(untitled) - Estevanato, L. L. C.; Da Silva, J. R.; Falqueiro, A. M.; Mosiniewicz-Szablewska, E.; Suchocki, P.; Tedesco, A. C.; Morais, P. C.; Lacava, Z. G. M. (Int. J. Nanomed., 2012)

(untitled) - Sasikala, A. R. K.; Unnithan, A. R.; Park, C. H.; Kim, C. S. (J. Mater. Chem. B, 2016)

(untitled) - Liu, X. O.; Atwater, M.; Wang, J. H.; Huo, Q. (Colloids Surf., B, 2007)

(untitled) - Yu, H.; Chen, M.; Rice, P. M.; Wang, S. X.; White, R. L.; Sun, S. H. (Nano Lett., 2005)

(untitled) - Wei, Y.; Klajn, R.; Pinchuk, A. O.; Grzybowski, B. A. (Small, 2008)

(untitled) - Jin, Y.; Jia, C.; Huang, S.-W.; O'Donnell, M.; Gao, X. H. (Nat. Commun., 2010)